2022
DOI: 10.3390/ijerph19020745
|View full text |Cite
|
Sign up to set email alerts
|

HIV Knowledge and Stigmatizing Attitude towards People Living with HIV/AIDS among Medical Students in Jordan

Abstract: The stigmatizing attitude towards people living with HIV/AIDS (PLWHA) can be a major barrier to effective patient care. As future physicians, medical students represent a core group that should be targeted with focused knowledge and adequate training to provide patient care without prejudice. The aim of the current study was to examine HIV/AIDS knowledge, and the stigmatizing attitude towards PLWHA, among medical students in Jordan. The current study was based on a self-administered online questionnaire, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 71 publications
1
9
0
2
Order By: Relevance
“…Overall, students at clinical study level showed a better knowledge regarding HIV transmission routes compared to the preclinical study level ( Table 1 ), which is in agreement with studies by Sallam et al [ 25 ] and Al-Kadhim [ 26 ]. Although HIV transmission through saliva in the dental environment has not yet been established [ 27 ], only 41% of the dental students in our study were aware of this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, students at clinical study level showed a better knowledge regarding HIV transmission routes compared to the preclinical study level ( Table 1 ), which is in agreement with studies by Sallam et al [ 25 ] and Al-Kadhim [ 26 ]. Although HIV transmission through saliva in the dental environment has not yet been established [ 27 ], only 41% of the dental students in our study were aware of this finding.…”
Section: Discussionsupporting
confidence: 89%
“…This result was uniform across all sociodemographic and occupational categories. Although this finding does not necessarily imply a negative attitude towards MSM stricto sensu, it should be evaluated further especially in the Middle East region, where a few studies pointed to the generally negative attitude towards MSM in the context of HIV infection, besides the reporting of social stigma and bullying towards COVID-19 patients in the early phases of the pandemic [ 59 , 60 , 61 , 62 ]. This issue needs further evaluation in future studies, since in the words of the WHO Director General “stigma and discrimination can be as dangerous as any virus” [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence suggests mixed reports regarding the level of HIV/AIDS knowledge, attitude, and practice among university students ( 18 ), previous studies on students' HIV/AIDS knowledge, attitudes, and behaviors among undergraduates university and college students ( 19 21 ), and few studies have conducted HIV-/AIDS-related KAP survey among the freshmen. The purpose of this study is to understand the knowledge, attitudes, and sex education of freshmen from the Jiangsu colleges and universities, we also analyzed factors affecting the overall awareness rate of knowledge about HIV/AIDS and explore the relationship between sex knowledge, attitudes, and education.…”
Section: Introductionmentioning
confidence: 99%